Application of simulated teaching based on standardized case database combined with guided feedback in practical teaching of nursing undergraduates (基于标准化案例库的情景教学结合引导性反馈在护理本科生实践教学中的应用) - SONG YaLan (宋亚兰); WU Ting (吴婷) (中西医结合护理)
Objective To explore the application effect of simulated teaching based on standardized case database combined with guided feedback method in the practice teaching of nursing undergraduates. Methods Cluster sampling method was adopted to select 216 nursing undergraduates of 2016 in school as the research object. A standardized case database was established, and s simulated teaching combined with guided feedback method was adopted in the practice teaching of nursing undergraduates. The critical thinking and independent learning ability of nursing undergraduates before and after practical teaching were compared. Results After the implementation of scene simulation teaching based on standardized case database combined with guided feedback teaching mode, scores of assessments on critical thinking and independent learning ability of nursing undergraduates were improved, compared with those before intervention, the difference was statistically significant (P＜0. 05). Conclusion Scene simulation teaching based on standardized case database combined with guided feedback teaching mode can improve the critical thinking and independent learning ability of nursing undergraduates, which is worthy of promotion and application. (目的 探讨基于标准化案例库的情景教学结合引导性反馈在护理本科生实践教学中的应用效果。方法 采用整群抽样法, 选取本校2016级护理本科生216人作为研究对象。建立标准化案例库, 并在护理本科生实践教学中运用情景教学结合引导性反馈。评价护理本科生的评判性思维和自主学习能力。结果 实施基于标准化案例库的情景教学结合引导性反馈教学模式后, 护理本科生的批判性思维及自主学习能力各维度得分均有所提高, 与干预前相比, 差异有统计学意义(P＜0. 05)。结论 基于标准化案例库的情景教学结合引导性反馈教学模式, 能够提高护理本科生的批判性思维和自主学习能力。)